Abordaje integrativo del insomnio en atención primaria: medidas no farmacológicas y fitoterapia frente al tratamiento convencional - Viniegra Domínguez, M. Adela (Aten Primaria, 2015)
INTRODUCTION: Insomnia is a sleep disorder in which there is an inability to fall asleep or to stay asleep. At some point in life, 50% of adults suffer from it, usually in stress situations. AIM: To evaluate the impact of sleep hygiene measures, relaxations techniques, and herbal medicine to deal with insomnia, compared with standard measures (drug treatment). METHODOLOGY: An experimental, retrospective, non-randomized study was conducted by means of a review of patients diagnosed with insomnia (2008-2010). Patients in the intervention group (IG) received an integrative approach (hygiene measures, relaxation techniques, and herbal medicine) and a control group (CG) with conventional treatment. A comparison was made of the resources used in the two groups (average monthly visits pre- and post-diagnosis), type of prescribed drug therapy and total dose. Sleep quality was evaluated at 18-24 months (Epworth test). RESULTS: A total of 48 patients were included in the IG and 47 in the CG (70% women, mean age 46 years (SD: 14.3). Average monthly visit pre-diagnosis was 0.54 (SD: 0.42) in the IG and 0.53 (SD: 0.53) in the CG (P = .88). Post-diagnosis it was 0.36 (SD: 0.24) and 0.65 (SD: 0.46), respectively (P < .0001), with a statistically significant reduction being observed in the IG. More than half (52.5%) of the IG patients and 93.6% in the CG had received a benzodiazepine (P < .0001). Alprazolam and lorazepam were the most prescribed in the CG and with higher cumulative dose. In the subsequent evaluation, 17% of patients in the IG and 5% in CG did not have insomnia. Severe insomnia was present in 13% of patients in the IG and none in CG (P < .0001). CONCLUSIONS: The integrative approach to insomnia may be worthwhile as it reduces resource use and side effects, as well as dependence to benzodiazepines.